The future of humanity: bioethical challenges between eugenics and transhumanism - Rodríguez Saavedra, Liliana (2024)
The present study focused on an analysis of emerging technologies applied to human beings, exactly the “genetic improvement” also called liberal eugenics from the philosophical and scientific perspective. Taking as a starting point that transhumanism is the current of thought that is oriented to the desire to transform human beings through the direct use of technology and perhaps with these advances to improve and create a new, superior and evolved species, descendant of our lineage. The aim of this study was to analyze the bioethical implications of eugenics from a transhumanist point of view. We used the method of documentary review was used. The conclusions show that it is urgent that the sciences of the spirit, the social and human sciences impart and strengthen human principles and values in order to guide future generations and science on the path of truth, justice, human development, protection of nature and respect for human life.